The development of the FTMSK local instant messenger (FTMSK messenger) / Rafidah Binti Mohd Zawawi - Mohd Zawawi, Rafidah (2007)
The project is about developing a local FTMSK instant messenger that called FTMSK Messenger that will be used as one of the communication channel mainly in the discussion environment between students and lecturers of FTMSK. As instant messenger become one of the most preferable communication channel, the development of this local instant messenger hopefully will benefits the students and lecturers of FTMSK. There are some problems arise when we use other communication technology such as email and SMS service in which both cannot provide fastest response. The use of instant messenger will give us the fastest responses because it has the ability to show the status of other person who we want to communicate. The use of instant messenger will also reduce some cost such as the cost of sending the SMS. Other than that, by using the local instant messenger, it will reduce the possibilities of the internet security threats because the messenger will not connected to the internet instead connected locally. This messenger includes features such as connection to a server (client server architecture) by using the socket programming technology, registers new users (login), get the status or the availability of person, chatting (exchanging text messages), and participation on a conference. The use of java programming supports functionality including client/server communication through socket programming helps in developing this local instant messenger. The methodology used in developing the instant messenger is the system development life cycle (SDLC) consists of five stages which are project planning, analysis and requirement, design, development and testing.